Integrasi keilmuan interdisipliner pada Kurikulum UIN Raden Fatah Palembang - Ahmad Zainuri; K.A. Bukhori (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This article designates the change of IAIN Raden Fatah Palembang into UIN substantial changes in the structure of scientific buildings (epistemology of science) therein. The construction the epistemology of science integration is then called “rumah ilmu” (the